2010
DOI: 10.3855/jidc.1003
|View full text |Cite
|
Sign up to set email alerts
|

A survey of hand-washing facilities in the outpatient department of a tertiary care teaching hospital in India

Abstract: Introduction: Inadequate hand-washing facilities have been reported as a barrier to hand washing. This study aimed to evaluate the availability and accessibility of hand-washing facilities and supplies of hand-washing agents in the outpatient department (OPD) complex of a tertiary care teaching hospital. Methodology: A checklist containing 13 variables was prepared and all rooms of direct patient care in the OPD were assessed on one occasion. Results: Out of 211 rooms surveyed, a hand-washing facility was avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
4
17
1
Order By: Relevance
“…However, only 28% of the sinks were fully functional with water flowing from their taps all day. This is quite low when compared to reports from a similar study in India with 98% functional and accessible handwashing sinks [22]. Although our study had a low proportion of functional sinks, a similar Nigerian study found an even lower proportion (14.3%) [23].…”
Section: Discussioncontrasting
confidence: 86%
“…However, only 28% of the sinks were fully functional with water flowing from their taps all day. This is quite low when compared to reports from a similar study in India with 98% functional and accessible handwashing sinks [22]. Although our study had a low proportion of functional sinks, a similar Nigerian study found an even lower proportion (14.3%) [23].…”
Section: Discussioncontrasting
confidence: 86%
“…Greater dispersal near the faucet may be attributed to the specific designs of the sink bowl and faucet in this study, which determine the contact angle of water impact. This is an important finding since many sinks in hospitals are similar in design, with faucet handles representing a high-touch surface for the sink users (38). It can also be concluded from the dispersion experiments that secondary and successive dispersals would likely increase the degree and the scope of dispersion.…”
Section: Discussionmentioning
confidence: 67%
“…[22] In another study, personnel, as well as patients, should access to appropriate detergents and automatic valves as important factors for encouraging individuals wash their hand has been reported. [23] The lack of facilities for personnel hands washing will decrease their interest has shown. [24] Daily reports of infection associated with, could increase quantity and quality of hand washing.…”
Section: Hands Washing a Prerequisite For Infection Controlmentioning
confidence: 99%